2018
DOI: 10.1002/prot.25610
|View full text |Cite
|
Sign up to set email alerts
|

Exploring molecular mechanism of allosteric inhibitor to relieve drug resistance of multiple mutations in HIV‐1 protease by enhanced conformational sampling

Abstract: Recently, allosteric regulations of HIV-1 protease (PR) are suggested as a promising approach to relieve drug resistance of mutations toward inhibitors targeting the active site of PR. Replicaexchange molecular dynamics (REMD) simulations and normal mode analysis (NMA) are integrated to enhance conformational sampling of PR. Molecular mechanics generalized Born surface area (MM-GBSA) method was applied to calculate binding free energies of three inhibitors APV, DRV, and NIT to the wild-type (WT) and multidrug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…In order to identify the residues that play an important role in the binding of the DRV to proteases, in WT-Pr-D and MUT-Pr-D the MM-PBSA approach was used ( Supplementary Table S1 ; Figure 6 ). As seen, the residues A28, I50, I84, A28’, I50’, and I84’ of WT-Pr play an important role in binding to the DRV, which is consistent with the previously reported results ( Meher and Wang, 2012 ; Chen et al, 2018 ). On the other hand, the energy analysis also showed the main unfavorable binding energy of D25, D30, D29’, and G48 residues to DRV in WT-Pr.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In order to identify the residues that play an important role in the binding of the DRV to proteases, in WT-Pr-D and MUT-Pr-D the MM-PBSA approach was used ( Supplementary Table S1 ; Figure 6 ). As seen, the residues A28, I50, I84, A28’, I50’, and I84’ of WT-Pr play an important role in binding to the DRV, which is consistent with the previously reported results ( Meher and Wang, 2012 ; Chen et al, 2018 ). On the other hand, the energy analysis also showed the main unfavorable binding energy of D25, D30, D29’, and G48 residues to DRV in WT-Pr.…”
Section: Resultssupporting
confidence: 93%
“…Briefly, our results showed that the hydrogen bonding network was disturbed in MUT-Pr, leading to a decreased potency of DRV binding to the active site. This could cause resistance against DRV ( Chen et al, 2018 ; Henes et al, 2019 ), as discussed in Sections 3.3 and 3.4 .…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, multiple simulation methods, including conventional molecular dynamics (cMD), [54][55][56][57][58][59][60][61][62] replica-exchange molecular dynamics (REMD), 63,64 accelerated molecular dynamics (aMD) [65][66][67][68][69] and Gaussian accelerated molecular dynamics (GaMD) 70-78 etc., have been proposed to probe conformational changes of receptors because of ligand bindings and residue mutations. Compared to cMD, MR-GaMD simulations can obtain more rational conformational sampling on receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] From the perspective of the human immunodeficiency virus, the entity with the highest reported mutation rate, 6 it successfully fights continuous drug selective pressure, leading to the emergence of drug resistant forms. 7 Due to the absence of a successful anti-HIV vaccine and drawbacks of presently approved anti-HIV drugs, a design of a new drug candidates, with increased potency and less side effects (less toxic, increased pharmacokinetic properties) remains hot topic in scientific and pharmaceutical community, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] even 30 years after the first registered drug, azidothymidine. 25 Over the past 20 years, myriad of a quantitative structure-activity relationship (QSAR) studies were performed with the aim to design novel anti-HIV compounds.…”
Section: Introductionmentioning
confidence: 99%